Aspartames Alter Pharmacokinetics Parameters of Erlotinib and Gefitinib and Elevate Liver Enzymes in Wistar Rats - Hajer AlRasheed; Aliyah Almomen; Haya I. Aljohar; Maria Arafah; Rana Y. Almotawa; Manal A. Alossaimi; Nourah Z. Alzoman (MDPI AG, 2022)
Background: Erlotinib (ERL) and gefitinib (GEF) are extensively metabolized by CYP450 enzymes. Aspartame (ASP), an artificial sweetener, induces CYP2E1 and CYP3A2 enzymes in the brain and could increase liver enzymes. In this work, the influence of ASP on the pharmacokinetics (PK) of ERL and GEF in Wistar rats was evaluated. Methods: The PKs of ERL and GEF were evaluated after receiving 175 mg/kg or 1000 mg/kg of ASP for four weeks using UPLC-MS/MS. Levels of liver enzymes after four weeks of ASP consumption were also evaluated. Results: ASP 175 mg/kg was able to significantly alter levels of Cmax (36% increase for ERL, 38% decrease for GEF), AUC0-72 (205% increase for ERL, 41% increase for GEF), and AUC0-∞ (112% increase for ERL, 14% increase for GEF). Moreover, ASP 175 mg/kg decreased the apparent oral clearance ERL and GEF by 58% and 13%, respectively. ASP 1000 mg/kg increased Cmax of ERL by 159% and decreased GEF's Cmax by and 73%. Both AUC0-72 and AUC0-∞ were increased by ASP 1000 for ERL and decreased for GEF. CL/F decreased by 64% for ERL and increased by 38.8% for GEF. Moreover, data indicated that ASP significantly increased levels of liver enzymes within two weeks of administration. Conclusions: Although ASP 175 and 1000 mg/kg alter ERL and GEF PKs parameters, ASP 1000 mg/kg has the highest impact on most parameters. ASP 1000 mg/kg also can significantly increase activities of liver enzymes indicating the possibility of inducing liver injury. Therefore, it might be of clinical importance to avoid the administration of aspartame containing products while on ERL or GEF therapy.